A Perfectly Periodic Three‐Dimensional Protein/Silica Mesoporous Structure Produced by an Organism. (12th December 2013) - Zlotnikov, Igor; Werner, Peter; Blumtritt, Horst; Graff, Andreas; Dauphin, Yannicke; Zolotoyabko, Emil; Fratzl, Peter
<x xml:space="preserve">Abstract</x> The discovery of perfectly ordered 3D mesoporous protein/silica structure in the axial filament of the marine sponge Monorhaphis chuni is reported. The structure belongs to body‐centered tetragonal symmetry system (a = 9.88 nm, c = 10.83 nm) and comprises interconnecting lattices of protein and silica, templated by the self‐assembled, enzymatically active protein‐silicatein, whose primary function is the precipitation of silica. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>